The Turning Point : The Abstract Expressionists and the Transformation of American Art. - Kingsley, April; Kingsley, April (New York, London, Toronto, Sydney, Tokyo, Singapore : Simon & Schuster, 1992)
Abbott, Mary ; Albers, Josef ; Alfieri, Bruno ; Alloway, Lawrence ; Arensberg, Louise ; Arensberg, Walter ; Avery, Milton ; Azhe, Anton ; Barr, Alfred H. Jr. ; Baudelaire, Pierre Charles ; Baziotes, Ethel ; Baziotes, William ; Bearden, Romare ; Beaton, Cecil ; Beckett, Samuel ; Bellows, George ; Benton, Thomas Hart ; Berger, John ; Bergson, Henri ; Blake, William ; Bloom, Hyman ; Blume, Peter ; Bourdrez, Martha ; Bourgeois, Louise ; Bowles, Jane ; Bowles, Paul ; Boyer, Paul ; Brancusi, Constantin ; Braque, Georges ; Breton, André ; Brooks, James ; Browne, Rosaline Bengelsdorf ; Bultman, Fritz ; Bultman, Jeanne ; Burckhardt, Rudolph ; Busa, Peter ; Cage, John ; Calder, Alexander ; Callery, Mary ; Carone, Nick ; Cary, Joyce ; Cavallon, Giorgio ; Cecchetti, Enrico ; Cézanne, Paul ; Chareau, Pierre ; De Chirico, Giorgio ; Coates, Robert ; Cooper, Douglas ; Creeley, Robert ; d'Harnoncourt, René ; Dali, Salvador ; Davies, Gwen ; Davis, Miles ; Delacroix, Eugène ; Delaunay, Robert ; Denby, Edwin ; Devree, Howard ; Dickinson, Edwin ; Dillon, Josephine ; Dodge, Mabel ; Dondero, George ; Donnelly, Helen ; Dragon, Ted ; Dubuffet, Jean ; Duchamp, Marcel ; Dugmore, Ed ; Egan, Charles ; Ernst, Jimmy ; Ernst, Max ; Falkenberg, Paul ; Faulkner, William ; Ferber, Herbert ; Frankenthaler, Helen ; Frankfurter, Alfred M. ; Freas, Jean ; Freud, Sigmund ; Freudenberg, Phillip ; García Lorca, Federico ; Gasquet, Joachim ; Gatch, Lee ; Gaw, William ; Genauer, Emily ; Giacometti, Alberto ; Glarner, Fritz ; Glick, Bernard ; van Gogh, Vincent ; Goldman, Emma ; Goldstein, Lieb ; Goldstein, Rachel ; Goldwater, Robert ; Gonzales, Julio ; Goodnough, Robert ; Goodwin, Donald ; Goossen, Eugene ; Gorky, Agnes Magruder ; Gorky, Arshile ; Gorky, Marney George ; Gorky, Maro ; etc.
boek
Keywords: Amerika